Pupillometric and Perceptual Approaches Provide Independent Estimates of Melanopsin Activity in Humans - Didikoğlu, Altuğ; Woelders, T.; Didikoglu, A.; Bickerstaff, L.; Brown, T.M.; Lucas, R.J. (Oxford University Press, 2025)
Study Objectives: Melanopsin-expressing retinal ganglion cells, which provide light information to time sleep and entrain circadian clocks, also influence perceived brightness raising the possibility that psychophysical paradigms could be used to explore the origins and implications of variability in melanopic sensitivity. We aimed to develop accessible psychophysical tests of melanopic vision and relate outcomes with a pupillometric measure of melanopsin function (post-illumination pupil response) and prior light exposure. Methods: Individually calibrated pairs of isoluminant stimuli differing in melanopic radiance from a four primary source were presented sequentially with superimposed random color offsets in a two alternative forced choice brightness preference paradigm to 41 naïve adult participants with personal light exposure data for the prior 7 days and post-illumination pupil response measures defined by comparing maintained pupil constriction for luminance matched “red” vs “blue” pulses. Results: Across participants we observed the expected tendency to report positive melanopsin contrast stimuli as “brighter” (one-tailed t-test p < 0.001), but with substantial inter-individual variability in both sensitivity (melanopsin contrast at criterion preference p = 0.75) and amplitude (preference at maximum melanopic contrast). There was little correlation between these psychophysical outcomes and post-illumination pupil response magnitude, or between either psychophysical or post-illumination pupil response measures and light history metrics (pairwise Pearson correlation coefficients -0.5> < 0.5). Random forest machine learning failed to satisfactorily predict outcome for either psychophysical or post-illumination pupil response measures based upon these inputs. Conclusions: Our findings reveal that estimates of melanopic function provided by perceptual and pupillometric paradigms can be largely independent of one another and of recent history of light exposure. © The Author(s) 2024. Published by Oxford University Press on behalf of Sleep Research Society.
Keywords: Brightness; Contrast; Light Sensitivity; Melanopsin; Post-Illumination Pupil Response; Silent Substitution